Review Additive Manufacturing Methods for Thermal Energy Storage - Sukendar, Sukendar; Pranoto, Hadi (Institute for Research on Innovation and Industrial System (IRIS), 2025)
The field of energy storage is undergoing significant transformation through the integration of additive manufacturing (AM). However, current challenges persist in addressing the optimization of material properties, precision, and manufacturing constraints in thermal energy storage (TES) systems. The aim of this study is to review the advancements in AM techniques as applied to TES systems, focusing on their ability to enhance thermal efficiency, reduce material wastage, and improve economic viability. The methodology employed is a systematic literature review (SLR), consolidating findings from previous studies to identify the effectiveness of AM in fabricating TES components. Key findings highlight that AM enables the creation of complex structures, such as lattices and composite phase change materials (PCMs), that improve heat transfer, thermal conductivity, and system stability. For instance, optimized fin designs produced via AM have reduced conduction resistance by up to 17 times. Additionally, integrating lattice frameworks and porous matrices has enhanced energy storage capabilities by improving temperature uniformity and reducing phase change material melting times. AM demonstrates transformative potential in TES by enabling innovative designs and efficient material usage. However, further research is required to address scalability, cost-effectiveness, and high-resolution manufacturing to fully realize its application in industrial energy storage systems.